Avaliação do potencial energético de resíduos de produção agrícola provenientes do beneficiamento da mandioca e do milho - Alves, Darline Albuquerque de Holanda (2014)
Brazil is privileged with respect to the variety of agricultural and forestry crops, depending on the climate and also the good soil conditions country, and has a huge expanse of land available for cultivation of various plant species. This potential producer generates a huge amount of waste, both from agricultural activities as the timber. Such debris can, in most cases, cause environmental degradation. The use of alternative sources of energy to fossil fuels has been gaining prominence in Brazil and worldwide. An option to prevent the depletion of natural resources is to replace the wood in the ovens by direct burning of agricultural waste from this activity or other waste in nature. The existing agricultural biomass in Brazil is from different cultures, for example, corn and manioc. The work aims to quantify and characterize the agroindustrial waste from cassava and maize throughout the State of Alagoas, aiming its use for burning in furnaces flour mills of the wild region. Physicochemical analysis of the raw material fresh and briquette form were conducted primarily to assess the calorific value of the samples, and all analyzes were performed according to the ABNT. It were obtained for the samples in nature, calorific value of 16.79 MJ/kg for cassava peels, 19.00 MJ/kg for manioc, 19.17 MJ/kg for corncobs and 18.58 MJ/kg in maize straw. The briquettes samples had a slight decrease in the calorific value, with 16.73 MJ/kg, 18.89 MJ/kg, 18.92 MJ/kg and 18.44 MJ/kg of values obtained for cassava peels, manioc, corncobs and maize straw, respectively. Still, it can be observed that both the waste from the processing of cassava as the corn had relevant potential energy when compared to firewood, around 20.70 MJ/kg, being able to be a substitute for wood, both in commercial as environmental aspect.